2001
DOI: 10.1590/s0034-89102001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Housework, paid work and psychiatric symptoms

Abstract: ObjectiveTo evaluate the hypothesis that work burden, the simultaneous engagement in paid work and unpaid family housework, is a potential risk factor for psychiatric symptoms among women. Methods A cross-sectional study was carried out with 460 women randomly selected from a poor area of the city of Salvador, Brazil. Women between 18 to 70 years old, who reported having a paid occupation or were involved in unpaid domestic activities for their families, were eligible. Work burden-related variables were define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
(31 reference statements)
2
7
0
4
Order By: Relevance
“…Other explanations for the worse health status of married women can be advanced, although the present study cannot directly assess their importance. One important factor is the time and emotional commitments of married life and whether these demands have a negative affect on health (Santana, Loomis and Newman 2001). In a Brazilian study of the main care-givers of people who had recently suffered their first stroke and who had returned to their families with some ADL dependency, Karsch (2003) found that most care-givers were from the household (98 %) and were women (93 %) -and that among the women, 44 per cent were spouses and 31 per cent daughters.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations for the worse health status of married women can be advanced, although the present study cannot directly assess their importance. One important factor is the time and emotional commitments of married life and whether these demands have a negative affect on health (Santana, Loomis and Newman 2001). In a Brazilian study of the main care-givers of people who had recently suffered their first stroke and who had returned to their families with some ADL dependency, Karsch (2003) found that most care-givers were from the household (98 %) and were women (93 %) -and that among the women, 44 per cent were spouses and 31 per cent daughters.…”
Section: Discussionmentioning
confidence: 99%
“…Las empresas ilegales pequeñas, comunes en la economía informal, operan con procesos rudimentarios que pueden contribuir a una ocurrencia mayor de lesiones y enfermedades, y a aumentar el deterioro del medio ambiente (20). En contraste, en estudios de base comunitaria, en Brasil, no se encontraron diferencias en la incidencia de lesiones no fatales al comparar trabajadores informales con formales (21). Es posible que, en los países en desarrollo, la poca regulación laboral, las deficiencias en el acceso al sistema de salud laboral y la falta de programas preventivos eficientes para los trabajadores de la economía formal reduzcan las diferencias esperadas de morbilidad.…”
Section: Contratos De Trabajo No Tradicionales Y Consecuencias En La unclassified
“…Los trabajadores migrantes tienen mayor probabilidad de tener trabajos peligrosos y una prevalencia aumentada de abuso de alcohol (8). a pesar de la disminución de la mortalidad por accidentes laborales en comparación con los varones, las mujeres tienen mayor probabilidad de padecer enfermedades músculo-esqueléticas (24) y trastornos psicológicos (25) relacionados con el trabajo, problemas reconocidos como causas de discapacidades de larga duración, como así también mayor probabilidad de afrontar una doble carga de trabajo, al ocuparse de las tareas domésticas y del cuidado de los niños además de mantener un empleo, factor que se ha asociado con trastornos psicológicos leves (21).…”
Section: Contratos De Trabajo No Tradicionales Y Consecuencias En La unclassified
“…The relationship between gender and work has been explored throughout the study period but production has been scarce and centered in two institutions: Fiocruz, [16][17][18]78 and UFBA, through its two research groups -Programa de Estudos em Gênero e Saúde (MUSAGender and Health Studies Program) 6,9 and Programa de Investigação sobre a Saúde do Trabalhador (PISATProgram of Environmental and Worker's Health) 80,81 in the Instituto de Saúde Coletiva. On this theme, some epidemiological studies exploring the link between gender and health stand out, as does an update on breastfeeding from female workers' perspective.…”
Section: What the Scientific Production Is Aboutmentioning
confidence: 99%